2009
DOI: 10.1021/la901725f
|View full text |Cite
|
Sign up to set email alerts
|

QCM Operating in Threshold Mode as a Gas Sensor

Abstract: Application of the threshold mode allowed us to use the quartz resonator (quartz crystal microbalance, QCM) as a highly sensitive gas sensor measuring the forces of the rupture of adsorbed gas components from the resonator surface oscillating with increasing amplitude. This procedure allows one to analyze different gas components using the same surface modification, just varying the rupture threshold by varying the amplitude of shear oscillations. The sensitivity of the threshold measurements is 2 to 3 orders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Owing to their hybrid structure that includes both organic and inorganic components, NFM pore sizes and functionality can be tuned to a much greater extent than other nanoporous materials. NFM coatings on QCM,6a, 7 SAW,6 and MCL5 sensors demonstrate that gas detection is feasible 15. O 2 detection has received little attention to date, however, with the exception of luminescence quenching approaches 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their hybrid structure that includes both organic and inorganic components, NFM pore sizes and functionality can be tuned to a much greater extent than other nanoporous materials. NFM coatings on QCM,6a, 7 SAW,6 and MCL5 sensors demonstrate that gas detection is feasible 15. O 2 detection has received little attention to date, however, with the exception of luminescence quenching approaches 16.…”
Section: Introductionmentioning
confidence: 99%
“…A number of transduction mechanisms for O 2 sensing exists,1 including photoacoustic,2 optical,3 and chemiresistance methods 4. Sensors based on mass uptake using micro‐electro‐mechanical systems (MEMS) such as static microcantilevers (MCL),5 surface acoustic wave (SAW) devices,6 and quartz crystal microbalances (QCM),6a, 7 are particularly attractive due to their compact design, low power consumption, and low‐cost fabrication. Selective detection by such devices relies on the use of chemical recognition layers that can distinguish O 2 from other gases.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the research effort involving gas uptake by NFMs has focused on high-pressure (∼35 bar) storage applications, recent work has shown that NFMs could make ideal coating materials to enhance gas uptake and detection at low pressure. Chemical sensors based on mass uptake, such as the quartz crystal microbalance (QCM), , surface acoustic wave (SAW) sensors, and MEMS devices such as microcantilevers (MCL) employ transduction mechanisms that rely on an analyte being adsorbed by the device surface. Coating these device surfaces with a highly adsorbent material such as an NFM is therefore essential since the devices themselves have small surface areas and possess no inherent chemical specificity.…”
Section: Introductionmentioning
confidence: 99%
“…A mass change, particularly a mass increase, could be observed, if NH 3 molecules were adsorbed on the surface of CuBr. A quartz-crystal microbalance (QCM) was a typical gravimetric transducer for bio/chemical sensing that transformed the mass change of a foreign layer of an analyte into a frequency change of the QCM. When a solid film was immobilized on the QCM surface, the change in resonance frequency (Δ F ) would be proportional to the mass change (Δ m ) on the QCM surface, and this phenomenon was described and governed by the Sauerbrey equation . Therefore, the QCM device could be used to characterize the mass change of CuBr before and after the CuBr adsorbing NH 3 molecules.…”
Section: Introductionmentioning
confidence: 99%